Trigger Finger: A Narrative Review of Dynamic Ultrasound and Personalized Therapies - Donati, Danilo; Ricci, Vincenzo; Boccolari, Paolo; Tedeschi, Roberto; Origlio, Flavio; Vita, Fabio; Naňka, Ondřej; Catani, Fabio; Tarallo, Luigi (Journal of clinical ultrasound, 2025)
Trigger finger (TF) is a prevalent hand condition characterized by impaired tendon gliding and pulley thickening, leading to pain and functional limitations. This narrative review explores TF's functional assessment, sonographic findings, and conservative treatments. Tools like the Quinnell Grading System and Jamar Dynamometer effectively quantify severity and function, while ultrasound identifies hypoechoic A1 pulley thickening (> 0.62 mm) and tendon snapping. Conservative treatments, including splinting and tendon gliding exercises, reduce pain by 70% within weeks. Ultrasound-guided corticosteroid injections and percutaneous A1 pulley release improve outcomes with minimal complications. Integrating imaging and personalized therapies optimizes TF management, reducing surgical reliance.
Keywords: Trigger Finger Disorder; Fingers; šlachy; Ultrasonography; individualizovaná medicína; conservative treatment; trigger finger; lupavý prst; Precision Medicine; ultrasound; lidé; prsty ruky; Humans; tendon gliding; corticosteroid injection; Tendons; ultrasonografie